ANALISIS BREAK EVEN POINT DAN RISIKO PENDAPATAN USAHA KERUPUK IKAN GABUS DI KECAMATAN SERUYAN HILIR KABUPATEN SERUYAN KALIMANTAN TENGAH - Lili Winarti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
This study aims to analyze Break Even Point (BEP) and the risk of snakehead fish cracker business income in subdistrik seruyan hilir district seruyan, this research was conducted in March 2017 s / d June 2017 in sub district Seruyan Hilir Seruyan District. Sampling using census method or the entire population of snakehead fish cracker processing business owner in Seruyan Hilir Sub-district that actively producing snakehead fish cracker is sampled In this research, there are 14 people who are all sampled in research. The data analysis used was Break Even Point analysis and income risk from snakehead fish cracker business, based on the result of the average fixed cost analysis used Rp 7.095.803 per year and the average variable cost used was Rp 59.779.200 per year , And based on Break Even Point analysis of snakehead fish cracker business conducted for Break Even Point from production of fish snakehead crackers in one production process is 7.96 kg / production and Break Even Point based on sales obtained in one production is Rp 7.324. 303 and the result of risk analysis of snakehead fish cracker income based on business income risk for CV value of 0,17 (0,17 <0,5) and L> 3,749,920,75 (> 0), it can be interpreted that income risk the minimum obtained by the business of fish snakehead crackers in the run of Rp 3,749,920.75 / kg.